Testing Family Stress and Family Investment Explanations for Conduct Problems Among African American Adolescents. Issue 2 (5th January 2016) - Simons, Leslie Gordon; Wickrama, K. A. S.; Lee, T. K.; Landers‐Potts, Melissa; Cutrona, Carolyn; Conger, Rand D.
Abstract: The recent U.S. recession has resulted in higher rates of unemployment, underemployment, and child poverty, with African Americans disproportionately represented among the financially disadvantaged. Although past research has established the relationship between family financial hardship and various child adjustment problems, African Americans remain an understudied group. In the current study the authors used longitudinal data from the Family and Community Health Study ( n = 422), an all African American sample, to investigate the impact of economic distress on adolescent conduct problems. They examined the extent to which this relationship can be explained by 2 frequently employed models: (a) the family stress model and (b) the family investment model. The authors extend past research by assessing the relative contributions of each model while controlling for the paths proposed by the other model. The results suggest that the family processes identified by the family stress model provide a more accurate explanation for why economic hardship is associated with increased conduct problems among African American adolescents.